2021
DOI: 10.3390/ijerph182111663
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effect of Yoga Practice on Physical Fitness in the Elderly

Abstract: The purpose of this study was to meta-analyze the effects of yoga intervention on physical fitness in the elderly. The following databases were systematically searched in 25 March 2021: Cochrane, PubMed and Embase. A total of 656 papers was identified through key word combinations, finally, 12 studies were included in the meta-analysis. The main conclusions are as follows. First, yoga practice showed moderately positive effects on muscle strength, balance, mobility, and lower body flexibility, but had no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Our results were consistent with previous systematic reviews showing yoga benefits on muscle strength and cardiorespiratory fitness among the general population, elderly, and individuals with overweight or obesity [ 22 , 51 , 52 , 53 ]. Previous meta-analyses found a moderate effect size of yoga on muscle strength but there was heterogeneity [ 22 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results were consistent with previous systematic reviews showing yoga benefits on muscle strength and cardiorespiratory fitness among the general population, elderly, and individuals with overweight or obesity [ 22 , 51 , 52 , 53 ]. Previous meta-analyses found a moderate effect size of yoga on muscle strength but there was heterogeneity [ 22 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results were consistent with previous systematic reviews showing yoga benefits on muscle strength and cardiorespiratory fitness among the general population, elderly, and individuals with overweight or obesity [ 22 , 51 , 52 , 53 ]. Previous meta-analyses found a moderate effect size of yoga on muscle strength but there was heterogeneity [ 22 , 51 ]. The presence of medical conditions could be the source of clinical heterogeneity in the previous studies since our meta-analysis did not find any heterogeneity among patients with T2DM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In elderly cohorts, declining muscle function is a major contributor to falls risk and reduced ability to perform activities of daily living [ 67 ]. Meta-analyses examining the effects of yoga in the elderly population reported improved physical fitness, muscle strength, power, endurance, flexibility in those in their 60 s and 70 s [ 57 , 67 ].…”
Section: Benefits Of Yoga On Function In the Elderlymentioning
confidence: 99%
“…In elderly cohorts, declining muscle function is a major contributor to falls risk and reduced ability to perform activities of daily living [ 67 ]. Meta-analyses examining the effects of yoga in the elderly population reported improved physical fitness, muscle strength, power, endurance, flexibility in those in their 60 s and 70 s [ 57 , 67 ]. In a study of 7 trials with 1033 participants, bi-weekly 45 min yoga sessions showed a significant improvement in fatigue in the elderly, at 3 months post-intervention when compared to controls [SMD: − 0.40, 95% CI − 0.62 to − 0.18], though this effect did not persist long-term [ 68 ].…”
Section: Benefits Of Yoga On Function In the Elderlymentioning
confidence: 99%